Peran Kader Posyandu sebagai Fasilitator Penguatan Pola Asuh Keluarga dalam Pencegahan Stunting di Desa Nagrak - Aisyah, Siti; Suherman, Maman (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Stunting remains a major public health challenge that requires not only health-service interventions but also sustained family and community engagement. This study aimed to analyze the role of Posyandu cadres as facilitators in strengthening family parenting practices for stunting prevention in Nagrak Village, Darangdan District, Purwakarta Regency. A descriptive qualitative approach with a case study design was employed. The study involved 16 purposively selected informants consisting of 10 Posyandu cadres, five mothers of children under five, and one coordinating midwife. Data were collected through semi-structured interviews, observations conducted at seven Posyandu units, and documentation. Data analysis involved transcription, coding, categorization, thematic interpretation, data display, and conclusion drawing. Data trustworthiness was strengthened through source and technique triangulation, member checking, and an audit trail. The findings revealed that Posyandu cadres performed interconnected roles in nutrition education, facilitation of Posyandu services, basic consultation and family parenting support, child growth monitoring, digital communication through WhatsApp, and coordination with midwives and community health centers. These roles were supported by village government involvement, adequate Posyandu facilities, cadre training, and collaboration with health professionals. However, several constraints remained, including uneven maternal participation, limited family understanding of complementary feeding and nutrition, variations in digital access, and limited cadre competence in advanced nutrition counseling. The study concludes that Posyandu cadres function not merely as technical service providers but as community-based facilitators who connect health information, professional services, and everyday family practices. Strengthening communication, counseling, growth-monitoring, and referral competencies is therefore essential to optimize their contribution to stunting prevention. Abstrak: Stunting merupakan masalah gizi kronis yang membutuhkan intervensi tidak hanya melalui pelayanan kesehatan, tetapi juga melalui penguatan kapasitas keluarga dan masyarakat. Penelitian ini bertujuan menganalisis peran kader Posyandu sebagai fasilitator dalam pencegahan stunting melalui edukasi gizi, penguatan pola asuh keluarga, konsultasi, pendampingan, dan pemantauan pertumbuhan balita di Desa Nagrak, Kecamatan Darangdan, Kabupaten Purwakarta. Penelitian menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Informan berjumlah 16 orang yang terdiri atas 10 kader Posyandu, lima ibu balita, dan satu bidan koordinator. Data dikumpulkan melalui wawancara semi-terstruktur, observasi pada tujuh Posyandu, dan dokumentasi, kemudian dianalisis melalui proses pengodean, kategorisasi, penyajian tematik, dan penarikan kesimpulan. Keabsahan data dijaga melalui triangulasi sumber dan teknik serta member checking. Hasil penelitian menunjukkan bahwa kader berperan dalam edukasi mengenai gizi, 1.000 Hari Pertama Kehidupan, makanan pendamping ASI, kebersihan, dan pemantauan pertumbuhan; memfasilitasi pelayanan Posyandu; memberikan konsultasi dasar mengenai pengasuhan; menggunakan WhatsApp sebagai media komunikasi; serta menghubungkan keluarga dengan bidan dan Puskesmas. Peran tersebut didukung oleh fasilitas Posyandu, pemerintah desa, pelatihan kader, dan koordinasi tenaga kesehatan, tetapi masih menghadapi hambatan berupa rendahnya partisipasi sebagian keluarga, keterbatasan literasi gizi, dan kemampuan konseling kader. Penelitian ini menegaskan bahwa kader Posyandu berfungsi sebagai penghubung antara pelayanan kesehatan dan perubahan perilaku keluarga dalam pencegahan stunting berbasis masyarakat.